Studi Laboratorium Pengaruh Penggunaan Fluida Komplesi CaBr2 Terhadap Sifat Fisik Batuan Sandstone Sintetik - Amry Nisfi Febrian; M. G. Sri Wahyuni; Listiana Satiawati (PROSIDING SEMINAR NASIONAL CENDEKIAWAN, 2015)
Completion fluid has a good development in now days. One of some completion fluid is CaBr2. In this paper will explain how the effectivities of this completion fluid to porosity and permeability of sandstone. The influence of CaBr2 completion fluid to permeability of water, permeability of crude oil, and wettabilities of sandstone. And than this study can be used for a oil and gas activities.